Repurposing existing products to accelerate injury recovery (REPAIR) of military relevant musculoskeletal conditions - Clark, Andrew R.; Mauntel, Timothy C; Goldman, Stephen M; Dearth, Christopher L. (Frontiers in Bioengineering and Biotechnology, 2023)
Musculoskeletal injuries (MSKIs) are a great hindrance to the readiness of the United States (U.S.) Armed Forces through lost duty time and reduced operational capabilities. While most MSKIs result in return-to-duty/activity with no (functional) limitations, the healing process is often long. Long healing times coupled with the high frequency of MSKIs make them a primary cause of lost/limited duty days. Thus, there exists an urgent, clinically unmet need for interventions to expedite tissue healing kinetics following MSKIs to lessen their impact on military readiness and society as a whole. There exist several treatments with regulatory approval for other indications that have pro-regenerative/healing properties, but few have an approved indication for treating MSKIs. With the immediate need for treatment options for MSKIs, we propose a paradigm of Repurposing Existing Products to Accelerate Injury Recovery (REPAIR). Developing treatments via repurposing existing therapeutics for other indications has shown monumental advantages in both cost effectiveness and reduced time to bring to market compared to novel candidates. Thus, undertaking the needed research efforts to evaluate the effectiveness of promising REPAIR-themed candidates has the potential to enable near-term solutions for optimizing MSKI recovery, thereby addressing a top priority within the U.S. Armed Forces. Herein, the REPAIR paradigm is presented, including example targets of opportunity as well as practical considerations for potential technical solutions for the translation of existing therapeutics into clinical practice for MSKI.